Deteksi Dini Tumbuh Kembang Anak Usia Dini untuk Mencegah Stunting di Masa Keemasan Perkembangan Anak - Khadijah Khadijah; Homsani Nasution; Amanah Putri Fadillah; Andina Zahra; Fannia Sri Juwita; Nia Alfiyalawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Stunting is a chronic nutritional problem that remains a major challenge in improving the quality of human resources in Indonesia. This condition not only impacts children's physical growth but also their cognitive, social, and emotional development. This study aims to assess the effectiveness of early detection of childhood growth and development in stunting prevention efforts. The study used a quantitative approach with a cross-sectional design in children aged 24–59 months in the working area of Community Health Center X. Data were collected through questionnaires, anthropometric measurements, and observations of early detection implementation in the field. The results indicate that early detection of growth and development plays a crucial role in identifying stunting risks early through height and weight measurements and regular child development checks. Factors such as maternal nutrition during pregnancy, immunization history, environmental sanitation, and family roles significantly contribute to child growth and development outcomes. Stunting prevention efforts must be carried out comprehensively through a multi-sectoral approach involving families, communities, health workers, and the government, particularly in the implementation of the SDIDTK program and the 1000 HPK monitoring. The results of this study are expected to serve as a basis for strengthening early detection programs and increasing public awareness of the importance of stunting prevention from pregnancy.